Pesantren Sehat: Membangun Generasi Muda yang Peduli Kesehatan melalui Pembentukan Kader Kesehatan Remaja Sebaya - Christina, Tri Yahya; Sri Yulianti, Tunjung; Sriwiyati, Lilik; Safaruddin; Juni Andika, I Putu; Catur Sukmono, Antonius; Wianti, Sri; Sandramustika, Agustina (LOSARI DIGITAL, 2024)
Abstract. Mentoring adolescent students who are in a period of physical and psychological preservation is very important. This community service aims to form adolescent health cadres to build a young generation who care about health through peer cadres Kholifatullah Singo ludiro Islamic Boarding School. Considering that they are far from their families and live with fellow students of the same age. The method used is cadre formation and training. Cadres are formed from active students and the students' willingness to become peer adolescent health caders. Cadres are equipped with knowledge and skills through training related to adolescent health, basic care skills, and Focus Group Discussions (FGD) as provisions for cadres to be critical of students' health problems and increase cadres' self-confidence in providing education and motivation. The results obtained were the formation of 10 peer adolescent health cadres, consisting of 3 male cadres and 7 female cadres. These results are in accordance with the needs of the Islamic boarding school where most of the health problems, both physical and psychological, found were from female students. The results of the activity also showed an increase in knowledge and skills of cadres related to adolescent health. As students who do not yet have a background in health knowledge, cadres show a good understanding of adolescent health after receiving training. With the formation of cadres who have knowledge and skills related to adolescent health, cadres can become quality promotive, preventive, curative and rehabilitative for the health of adolescents of the same age as students. Keywords: Health Cadres; Healthy Islamic Boarding School; Youth Cadres; Youth Abstrak. Pendampingan remaja santri yang sedang dalam masa peralihan baik fisik maupun psikologis sangat penting. Pengabdian masyarakat ini bertujuan untuk membentuk kader kesehatan remaja sebaya santri untuk membangun generasi muda yang peduli kesehatan melalui kader sebaya Pesantren Kholifatullah Singo ludiro. Mengingat mereka jauh dengan keluarga dan tinggal bersama sesama santri sebaya. Metode yang digunakan adalah pembentukan kader dan pelatihan. Kader dibentuk dari santri yang aktif serta kesuka relaan dari santri untuk menjadi kader kesehatan remaja sebaya. Kader dibekali pengetahuan dan keterampilan/ skill melalui pelatihan terkait kesehatan remaja, keterampilan perawatan dasar, serta Focus Group Discussion (FGD) sebagai bekal kader untuk kritis terhadap masalah kesehatan santri serta meningkatkan kepercayaan diri kader dalam memberikan edukasi dan motivasi. Hasil yang didapat adalah terbentuknya 10 kader kesehatan remaja sebaya, dimana terdiri dari 3 kader laki- laki dan 7 kader perempuan. Hasil ini sesuai dengan kebutuhan Pesantren dimana sebagian besar permasalahan kesehatan baik fisik maupun psikologis yang ditemukan adalah dari santri perempuan. Hasil kegiatan juga menunjukkan adanya peningkatan pengetahuan maupun keterampilan/skill kader terkait kesehatan remaja. Sebagai santri yang belum memiliki latar belakang pengetahuan kesehatan, kader menunjukkan pemahaman yang baik terkait kesehatan remaja setelah mendapat pelatihan. Dengan terbentuknya kader yang memiliki pengetahuan dan keterampilan/skill terkait kesehatan remaja, kader dapat menjadi promotif, preventif, kuratif maupun rehabilitatif yang berkualitas untuk kesehatan remaja sebaya santri. Kata kunci: Kader Kesehatan; Kader Remaja; Pesantren Sehat; Remaja